EVALUASI PELAYANAN SOSIAL MASJID KECAMATAN KOTO TANGAH PADANG SUMATERA BARATf the Social Service for the Mosque of the Koto Tangah Subdistrict, Padang, West Sumatra - Rafelyna Afrilla; Yurni Suasti (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
The purpose of this study were (1) to see the function of social services in the mosque of Koto Tangah Padang District, West Sumatra (2) to analyze the social services of the mosque in the Koto Tangah District of Padang, West Sumatra. The research method used is descriptive qualitative research. Data collection techniques in this study are by means of observation, interviews and documentation. Data analysis techniques are by paying attention to data, data reduction, data presentation and data retrieval. The results of this study are (1) notification that mosque-based social service programs carried out by mosques in general are still conventional services. (2) Knowing the extent of the reach of the mosque's socio-economic services according to the theoretical reach radius of 400 meters and field surveys.